Sol-Gel Method - Recent Advances 2023
DOI: 10.5772/intechopen.111844
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Production of Semiconductor Metal Oxides for Gas Sensor Applications

Abstract: As they are widely utilized in industries including the food packaging industry, indoor air quality testing, and real-time monitoring of man-made harmful gas emissions to successfully combat global warming, reliable and affordable gas sensors represent enormous market potential. For environmental monitoring, chemical safety regulation, and many industrial applications, the detection of carbon monoxide (CO), carbon dioxide (CO2), nitrogen dioxide (NO2), and methane (CH4) gases is essential. To reliably and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…In addition, it has been found that defects and internal stress can broaden the XRD peak, so the actual value of crystallite size is higher than the average size calculated with Scherer's formula [48,49]. Nanomaterials-based zinc oxide has some advantages such as high sensitivity and selectivity, lower time, and accurate detection [50]. In another research, the combination of sol-gel synthesis for nucleation and hydrothermal preparation for growing zinc oxide nanorods on a polyethylene terephthalate substrate coated with tin oxide has been successfully applied to fabricate a wurtzite hexagonal structure in nanoscale (entire process under 100 °C) [51].…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…In addition, it has been found that defects and internal stress can broaden the XRD peak, so the actual value of crystallite size is higher than the average size calculated with Scherer's formula [48,49]. Nanomaterials-based zinc oxide has some advantages such as high sensitivity and selectivity, lower time, and accurate detection [50]. In another research, the combination of sol-gel synthesis for nucleation and hydrothermal preparation for growing zinc oxide nanorods on a polyethylene terephthalate substrate coated with tin oxide has been successfully applied to fabricate a wurtzite hexagonal structure in nanoscale (entire process under 100 °C) [51].…”
Section: Sol-gel Methodsmentioning
confidence: 99%